EFFECTIVE WAYS OF TREATMENT OF HIDDEN CHRONIC ENDOMETRITIS IN CATTLE IN KARAKALPAKSTAN (Academicia Globe: Inderscience Research, 2021)
In this article, we examined the causes of the occurrence of latent chronic endometritis, which occurs in cows, the results of a laboratory examination, a biopsy of the uterine mucosa, and the results of histological examinations. We focused our experiments on treatment based on levofloxacin antibiotics, and ultimately proved in experiments the effective outcome of the treatment of latent chronic endometritis of cattle.